An empirical examination of EFL learners' perceptual learning styles and acceptance of ASR-based computer-assisted pronunciation training. Issue 5 (3rd July 2016) - Hsu, Liwei
Abstract : This study aims to explore the structural relationships among the variables of EFL (English as a foreign language) learners' perceptual learning styles and Technology Acceptance Model (TAM). Three hundred and forty-one ( n = 341) EFL learners were invited to join a self-regulated English pronunciation training program through automatic speech recognition (ASR) computer system. Participants were asked to actively undertake the interactions with ASR-based computer-assisted pronunciation training (CAPT) on a daily basis for three months. They were directed to finish a questionnaire on their perceptual learning style and technology acceptance. The collected data were analysed with descriptive statistics and structural equation model to investigate the structural relationships. Results show that most participants were visual learners; furthermore, no significant relationship between any type of perceptual learning style and perceived usefulness was discovered. Visual style as well as kinaesthetic style was found to be significantly influential to perceived ease of use which further significantly led to perceived usefulness. Perceived usefulness was significantly related to attitude of using the system that was decisive to EFL learners' continuing use of ASR-based CAPT.